ANALISIS KINERJA KEUANGAN PT GARUDA METALINDO TBK MENGGUNAKAN METODE ECONOMIC VALUE ADDED PERIODE 2016 - 2019 - Heru Satria Rukmana; Mutiara Hulwah (Economicus : Jurnal Ekonomi dan Manajemen, 2022)
Based on the results of the study, it can be concluded that the financial performance of PT Garuda Metalindo Tbk for the period 2016 to 2019 which was analyzed by using the Economic Value added (EVA) method or value economic added as a whole results in a negative value that means that the company's financial performance is in an unhealthy state. In accordance with what has been determined if EVA < 0, performance The company's finances can be said to be not good because the company failed to increase economic value added. Financial performance at PT. Garuda Metalindo Tbk produced in 2016 until 2019 can be said to be negative (Eva < 0), because it shows that there is no economic value added process (NITAMI) for the company. The negative EVA value condition (EVA < 0 ), the company's financial performance is said to be unhealthy because the company cannot provide added value. In this case employees cannot get bonuses, only permanent creditors earn interest and share owners do not get a return commensurate with what was planted.